„Odgadnąć i uzewnętrznić wielką tajemnicę […] Chopinowskiej muzyki” – Dusze niektórych melodii. Chopin Cezarego Jellenty - Orłowska, Karolina (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article constitutes a detailed analysis and interpretation of one of the most important texts written at the turn of the twentieth century, which was devoted to the reception and interpretation of Frédéric Chopin’s compositions in the Young Poland period. In his work, Cezary Jellenta presents the nervous perception of the Polish composer’s music typical of the era and refers in his reflections to numerous works of painting and both Polish and world literature, which perfectly illustrates the fascination with the idea of the correspondence of arts. It is also a testimony to the foundations of the emerging music criticism and evidence of the undying adoration for Frédéric Chopin’s works.